Corneal epithelial basement membrane: Structure, function and regeneration. (May 2020) - Wilson, Steven E.; Torricelli, Andre A.M.; Marino, Gustavo K.
Abstract: Basement membranes are highly specialized extracellular matrices. More than providing scaffolds, basement membranes are recognized as dynamic and versatile structures that modulate cellular responses to regulate tissue development, function, and repair. Increasing evidence suggests that, in addition to providing structural support to adjacent cells, basement membranes serve as reservoirs and modulators of growth factors that direct and fine-tune cellular functions. Since the corneal stroma is avascular and has a relatively low keratocyte density, it's likely that the corneal BM is different in composition from the BMs in other tissues. BMs are composed of a diverse assemblage of extracellular molecules, some of which are likely specific to the tissue where they function; but in general they are composed of four primary components—collagens, laminins, heparan sulfate proteoglycans, and nidogens—in addition to other components such as thrombospondin-1, matrilin-2, and matrilin-4 and fibronectin. Severe injuries to the cornea, including infection, surgery, and trauma, may trigger the development of myofibroblasts and fibrosis in the normally transparent connective tissue stroma. Ultrastructural studies have demonstrated that defective epithelial basement membrane (EBM) regeneration after injury to the cornea underlies the development of myofibroblasts from both bone marrow- and keratocyte-derived precursor cells. Defective EBM permits epithelium-derived and tear-derived transforming growth factor beta (TGF-β), platelet-derived growth factor (PDGF), and possibly other modulators, to penetrate the stroma at sustained levels necessary to drive the development and persistence of vimentin + alpha-smooth muscle actin + desmin+ (V + A + D+) mature myofibroblasts. A recent discovery that has contributed to our understanding of haze development is that keratocytes and corneal fibroblasts produce critical EBM components, such as nidogen-1, nidogen-2 and perlecan, that are essential for complete regeneration of a normal EBM once laminin secreted by epithelial cells self-polymerizes into a nascent EBM. Mature myofibroblasts that become established in the anterior stroma are a barrier to keratocyte/corneal fibroblast contributions to the nascent EBM. These myofibroblasts, and the opacity they produce, often persist for months or years after the injury. Transparency is subsequently restored if the EBM is fully regenerated, myofibroblasts are deprived of TGF-β and undergo apoptosis, and keratocytes reoccupy the anterior stroma and reabsorb the disordered extracellular matrix. Highlights: Major components of the EBM are collagens, laminins, perlecan, and nidogens. Keratocytes and corneal fibroblasts contribute components during EBM regeneration. The EBM regulates the localization of TGFβ, PDGF, HGF and KGF. Defective regeneration of the EBM underlies stromal fibrosis.